The role of triple therapy and therapy sequence in treatment of BRAF-mutant metastatic melanoma. Response to overall survival with first-line atezolizumab in combination with vemurafenib and cobimetinib in BRAFV600 mutation-positive advanced melanoma (IMspire150): second interim analysis of a multicentre, randomised, phase 3 study - Reinhard Dummer; Michèle Welti; Egle Ramelyte (Journal of Translational Medicine, 2023)
Abstract Novel therapies have achieved unprecedented benefit in survival of advanced melanoma patients. While immunotherapy (ICI) can be administered independent of mutational status, BRAF and MEK kinase inhibitors represent another effective treatment option for patients with BRAF mutant melanoma. Given the benefits these therapies demonstrate, the natural instinct was to combine. Three studies have investigated the benefit of combination of ICI using anti-PD-1 or anti-PD-L1 antibody and targeted therapy (TT) with BRAF and MEK inhibitors over TT and placebo. Among these studies, statistically significantly superior duration of response was observed, however overall and progression-free survival were only numerically superior, if at all. One triple combination was approved for BRAF mutant metastatic melanoma; however, the expected synergistic effect of triple therapy could not be universally confirmed and the observed benefits with triple seem to depend on statistical considerations rather than a biological reason. As patients with BRAF mutant melanoma have both ICI and TT as their first-line treatment options, the question whether the sequence matters was addressed. Two prospective trials compared first-line ICI, followed by TT at progression, or vice-versa, with additional “sandwich” approach (8 weeks of TT followed by ICI until progression, then TT again) in the Secombit study. The benefit of first-line ICI was demonstrated in both studies with Secombit study showing the “sandwich” approach to have similar effect. Current data advices for immunotherapy based regiments in patients with BRAF mutant melanoma or, possibly, sandwich approach. Whether triple therapy is superior to ICI monotherapy still needs to be addressed considering not only efficacy, but also safety.